Enhancement of electricity generation and wastewater treatment by microbial fuel cell - Ali, Ayoub Ahmed
Microbial fuel cells (MFCs) are devices that use prokaryotic microorganism to produce electrical bioenergy from a wide range of organic substrates. MFCs provide a promising sustainable energy production as well as, simultaneous degradation of organic waste in the substrate. The active microorganisms capable of producing electricity by transferring an electron to the electrode are called Electrochemically Active Bacteria (EAB). In this study, the substrate used was water and mud collected from Malaysia's shrimp pond at Perak. A special U-shaped MFC reactor with carbon-based electrodes was used for screening and isolation the electrochemically active bacteria. In addition, most of the EAB isolated from MFC electrode are known as dissimilatory metal-reducing bacteria (DMRB), thus agar nutrient containing metal has been used for isolation. DMRB based isolation methods limited the potential isolation of diverse electrochemical bacteria. Therefore, in this study agar nutrient has been used for the isolation of the EAB from the anode electrode of the U-tube MFC. Where the pure culture obtained was Bacillus cereus strain cc-1 identified by using 16s rRNA genes. Next, the Bacillus cereus strain cc-1 was mutated using gamma irradiation in order to increase the activity of bacteria. The optimum dose to increase the bacteria potential has been determined using one factor at time (OFAT) method. Results show that 63Gy gamma dose irradiation increased the cell voltage to 280 mV with 33% of chemical oxygen demand removal (COD) while the maximum voltage of the wild strain was154 mV with 55.7% of COD removal. The successful effect of gamma radiation dose on the increase of the MFC's bioelectricity and organic matter removal indicates that gamma rays are a way to boost the ability of the electrically active bacteria. Further investigation on the whole genome sequencing analysis should provide the full picture of the gamma radiation-induced effect.